A facile soft template method to synthesize hollow carbon and MnOx composite particles for effective methylene blue degradation. Issue 50 (10th August 2018) - Meng, Qingnan; Du, Lulu; Ji, Yeye; Tang, Yufei; Han, Zhenhua; Zhao, Kang; Zhang, Guojun
Abstract : Hollow carbon and MnO x composite particles were synthesized for catalytic use and their formation mechanism was proposed. Abstract : Hollow carbon and MnO x composite particles (HC-Mn) were fabricated by using polyacrylic acid (PAA) and Mn ion co-assembled colloids as the soft template and resorcinol formaldehyde resin (RF) as the carbon source. The formation process was well studied and a plausible formation mechanism was proposed. The Mn ions played two key roles in the synthesis: first, they promoted the aggregation of the PAA molecules, thus forming the PAA–Mn colloids in solution with high water content, which were suitable for the subsequent RF coating. Secondly, considerable Mn ions were retained after template removal, which were transformed into MnO x particles simultaneously during carbonization. This approach was facile and effective and the as-prepared HC-Mn showed superior catalytic activity toward methylene blue (MB) degradation.